Dari Kelas ke Industri: Apa yang Benar-Benar Meningkatkan Green Skills di Sekolah Menengah Kejuruan (SMK) Indonesia? - Dimas Aulia Saputra; Tuti Suartini; Tiara Maulida Yanti; Sri Lestari Harja; Sri Alvina Damayanti (Postgraduate, University of Mataram, 2026)
Indonesia's green transition requires vocational graduates who are not only technically competent, but also possess green skills (GS) in the cognitive (CC), interpersonal (IC), and intrapersonal (IaC) domains. This study aims to map the level of GS, patterns between domains, and learning factors in Indonesian vocational education by conducting a quantitative secondary synthesis of five Scopus-indexed studies (2015-2025). The methods used include structured book coding, metric harmonization, and the SWiM framework with voice calculation based on effect direction (↑, →, ↓, NR). The results show a gap between students and teachers: the average GS scores of students (2.188-2.594) were lower than those of teachers (2.242-2.917), with two of the three studies placing student GS in the low category. One intervention module showed a moderate improvement (N gain = 0.4; average score from 46.7 to 73.3). IC was consistently positive (3 out of 3 studies ↑), IaC was mixed (2 positive, 1 negative), and CC was varied (1 positive, 1 neutral, 1 negative). A survey of 562 Islamic vocational school students showed a positive relationship between religious and environmental values and GS. These findings highlight the importance of GS modules, values-based education, and green school culture.